2018
DOI: 10.1002/wat2.1325
|View full text |Cite
|
Sign up to set email alerts
|

Understanding microbial ecology to improve management of drinking water distribution systems

Abstract: Microorganisms in drinking water distribution systems (DWDS), and in particular the microbial communities that form biofilms on infrastructure surfaces, drive critical processes impacting water quality. This paper reviews knowledge, research approaches, and monitoring methods to consolidate understanding of the microbial ecology of DWDS. The review highlights how microbial characteristics and subsequent behavior can be broadly classified as common or complex. Common behavior relates to the ubiquitous and conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 78 publications
2
21
0
3
Order By: Relevance
“…The SNR of 5 in the recorded data allows us to clearly separate the polymer Raman lines from those of common biological contaminants like bacteria and microalgae [25,26,27]. While these microorganisms do have Raman lines in the spectral region used for identifying polymers, originating primarily from membranes and proteins within the cells [22,28], they are far weaker compared to the polymer Raman bands originating from the whole particle.…”
Section: Resultsmentioning
confidence: 99%
“…The SNR of 5 in the recorded data allows us to clearly separate the polymer Raman lines from those of common biological contaminants like bacteria and microalgae [25,26,27]. While these microorganisms do have Raman lines in the spectral region used for identifying polymers, originating primarily from membranes and proteins within the cells [22,28], they are far weaker compared to the polymer Raman bands originating from the whole particle.…”
Section: Resultsmentioning
confidence: 99%
“…Whether or not a disinfectant residual is present, a variety of water quality reactions are taking place between microorganisms (present in biofilms, sediments and free-floating in the water column), inorganic contaminants, such as corrosion byproducts, and nutrients. These complex reactions are influenced by source water quality (after treatment), hydraulic conditions in the DWDS (driven by customer demands), nature and condition of the infrastructure and temperature [4].…”
Section: Introductionmentioning
confidence: 99%
“…This bacterial order that presents interesting metabolic pathways, including carotenoid pigment synthesis (Siddaramappa et al, 2018), was found in various environments from the caves (Marques et al, 2019) to thermal springs (Pedron et al, 2019) and clouds (Amato et al, 2017), and recently, in the drinking water distribution system in Paris (Perrin et al, 2019). Microbial biofilm diversity and community composition have been addressed in several urban drinking and draining water distribution systems, and enrichments of specific communities within biofilms have been reported (Bertelli et al, 2018;Bruno et al, 2018;Douterelo et al, 2018;Douterelo et al, 2019;McLellan and Roguet, 2019). Interestingly, in the street gutter biofilms/ mats, we identified 21 OTUs (3 Arcobacter, 12 Acinetobacter, 5 Aeromonas and one Trichococcus) from genera that were previously shown to be dominant in sewer pipe (McLellan and Roguet, 2019).…”
Section: Discussionmentioning
confidence: 98%